Clinical Efficacy of Inhaled Nitric Oxide in Preventing the Progression of Moderate to Severe COVID-19 and Its Correlation to Viral Clearance: Results of a Pilot Study. Issue 1 (March 2022) - Moni, Merlin; Madathil, Thushara; Sathyapalan, Dipu T.; Menon, Veena; Gutjahr, Georg; Edathadathil, Fabia; Sureshkumar, Deepthi; Prasanna, Preetha; Jose, Soumya; Jerome, Roshni; Krishnan, Ajai; Pillai, Indulekha C.L.; et al.
Abstract : Abstract: Hypoxic patients with coronavirus disease 2019 (COVID-19) are at high risk of adverse outcomes. Inhaled nitric oxide (iNO) has shown anti-viral and immunomodulatory effects in vitro. However, in vivo evidence of efficacy in hypoxic COVID-19 is sparse. This open label feasibility study was conducted at a single referral center in South India and evaluated the effectiveness of repurposed iNO in improving clinical outcomes in COVID-19 and its correlation with viral clearance. We recruited hypoxemic COVID-19 patients and allocated them into treatment (iNO) and control groups (1:1). Viral clearance on day 5 favored the treatment group (100% vs 72%, P < 0.01). The speed of viral clearance as adjudged by normalized longitudinal cycle threshold (Ct) values was positively impacted in the treatment group. The proportion of patients who attained clinical improvement, defined as a ≥2-point change on the World Health Organization ordinal scale, was higher in the iNO cohort (n = 11, 79%) as compared to the control group (n = 4, 36%) (odds ratio 6.42, 95% confidence interval 1.09-37.73, P = 0.032). The proportion of patients progressing to mechanical ventilation in the control group (4/11) was significantly higher than in the treatment group (0/14). The all-cause 28-day mortality was significantly different among the study arms, with 36% (4/11) of the patients dying in the control group while none died in the treatment group. The numbers needed to treat to prevent an additional poor outcome of death was estimated to be 2.8. Our study demonstrates the putative role of repurposed iNO in hypoxemic COVID-19 patients and calls for extended validation.